Noa's earnings increase by $8,000 each year. We can express her earnings for each year using the following pattern:
- Year 1: $48,000
- Year 2: $56,000
- Year 3: $64,000
We can notice that the earnings form an arithmetic sequence where:
- First term (\(a\)) = $48,000
- Common difference (\(d\)) = $8,000
The formula for the \(n\)-th term of an arithmetic sequence is given by:
\[ a_n = a + (n-1) \cdot d \]
Substituting \(a\) and \(d\):
\[ a_n = 48000 + (n-1) \cdot 8000 \]
Simplifying this:
\[ a_n = 48000 + 8000(n-1) \] \[ a_n = 48000 + 8000n - 8000 \] \[ a_n = 40000 + 8000n \]
So, Noa's earnings in her \(n\)-th year will be:
\[ a_n = 8000n + 40000 \]
Therefore, Noa will make \(8000n + 40000\) in her \(n\)-th year working.